FROM CREDIBILITY TO CONSUMPTION: A CROSS CONTEXTUAL REVIEW OF PARASOCIAL INTERACTION AND PURCHASE INTENTION IN INFLUENCER MARKETING - Nia Widya Desinta (PT. Jurnal Center Indonesia Publisher, 2026)
The rapid advancement of digital technology has fundamentally reshaped consumer behavior globally, with social media becoming the primary channel for product information seeking. Approximately 51% of Indonesians rely on user reviews before purchasing, and 62% have bought products under the direct influence of Social Media Influencers (SMIs). Despite this, the psychological mechanisms linking influencer characteristics to purchase intention remain fragmented across sectors and platforms. This systematic literature review synthesizes nineteen empirical studies published between 2020 and 2025, spanning beauty, fashion, gadget, and sustainable product sectors across multiple countries, to examine how Source Credibility (attractiveness, trustworthiness, expertise) and Parasocial Interaction (PSI) jointly shape consumer purchase intentions. Three core findings emerge: (1) trustworthiness is the sole credibility dimension that is universally and consistently significant across all contexts, fundamentally challenging assumptions about the equal contribution of the three credibility dimensions; (2) PSI operates not as a single mediator but as a multi-pathway psychological bridge through hedonic value, brand attitude, vicarious experience, and social-personal value whose specific active pathway is contingent on platform, product type, and cultural context; and (3) generational and cultural moderators systematically shape which credibility dimension most powerfully drives PSI. A Proposed Integrative Conceptual Framework and a synthetic cross-study comparison matrix (Table 2) consolidate these findings. Results offer strategic implications for influencer marketing practice and identify priority directions for future research.